The psychological reactions after witnessing a killing in public in a Danish high school - Ask Elklit; Sessel Kurdahl (European Journal of Psychotraumatology, 2013)
Background: School killings attract immense media and public attention but psychological studies surrounding these events are rare. Objective: To examine the prevalence of posttraumatic stress disorder (PTSD) and possible risk factors of PTSD in 320 Danish high school students (mean age 18 years) 7 months after witnessing a young man killing his former girlfriend in front of a large audience. Method: The students answered the Harvard Trauma Questionnaire (HTQ), the Crisis Support Scale (CSS), and the Trauma Symptom Checklist (TSC). Results: Prevalence of PTSD 7 months after the incident was 9.5%. Furthermore, 25% had PTSD at a subclinical level. Intimacy with the deceased girl; feeling fear, helplessness, or horror during the killing; lack of expressive ability; feeling let down by others; negative affectivity; and dissociation predicted 78% of the variance of the HTQ total scores. Conclusion: It is possible to identify students who are most likely to suffer from PTSD. This knowledge could be used to intervene early on to reduce adversities.